A Comparison Of Pharmacological Treatment, Knowledge And Life Style Modification Among Diabetic Patients With Microalbuminuria In Four Hospitals In India And Malaysia - Baig, Mirza Rafiullah (2010)

(untitled)
Diabetic nephropathy is one of the major microvascular complications in diabetic patients. Epidemiologist predicts that the world population of diabetic individuals will swell up to an astounding 300 million by the year 2025 and almost half of that will be in the Asian region alone. Malaysia and India are ranked top in the list for the high prevalence of diabetes with India being termed as the “diabetes capital of the world”. Interventions have been extensively studied in different areas of diabetic complications, but still results remained unclear.